LEGAL REVIEW OF THE IMPLEMENTATION OF REGIONAL AUTONOMY POST-CONSTITUTIONAL AMENDMENT - Anwar Hidayat (INFOKUM, 2022)
Regional autonomy has become the main basis for developing democracy and inclusive governance in Indonesia. However, since the constitutional amendment, there have been significant changes in the legal framework governing regional autonomy. This research aims to analyze the Legal Review of the Implementation of Regional Autonomy after the Constitutional Amendment. This research is descriptive normative research using secondary data types which include primary legal materials, secondary legal materials and tertiary legal materials . The research results show that the second amendment to the 1945 Constitution in 2000 brought significant changes, including the importance of adding the principle of deconcentration in Article 18 paragraph (2) of the 1945 Constitution to clarify the authority between the central and regional governments at the lowest administrative level. Regional autonomy policies aim to decentralize power from the central government to the regions, allowing for significant shifts in power and providing opportunities for regions to better respond to the needs and aspirations of local communities. The formulation of Article 18 of the 1945 Constitution as a result of the Second Amendment in 2000 provides space for the development of pluralist autonomy policies, demonstrating a spirit of inclusiveness and recognition of diversity in Indonesia, as well as a commitment to strengthening the unity of the country while respecting the diversity and uniqueness of each region within it